L’écart dans l’œuvre de Percival Everett - Anne-Laure Tissut (Sillages Critiques)
Ethics and aesthetics meet in Percival Everett’s works, and transform our vision of deviation. From a condemnable parting from the norm, deviation becomes the dynamic principle of creation. Such shift in perspective requires that our reading modes be questioned. Reading now appears as a kind of translation, that opens itself to the strangeness and multilingual quality of any literary text.